ROLA EFEKTU PIERWSZEŃSTWA W PUBLIKACJACH PRASOWYCH - Wanat, Tomasz (Wydział Prawa i Administracji UAM, 2006)
Press articles are sometimes divided in two parts: the introductory one (the lead) and the main one. The paper is an attempt to determine the impact of the lead on the perception of information contained in the main part of a press article. The analysis of the order effect i.e. primacy, recency and the anchoring and adjustment heuristic constituted a theoretical basis. Hypotheses made on that basis were subsequently verified in the course of an experiment. It has been found that the division of a text into the lead and the main body does indeed influence the way in which the text is perceived. Despite identical content, the same text was perceived and evaluated differently, depending on the form of its presentation (divided or undivided). The sequencing of argumentation in the text has also proved to influence the way in which it is perceived. However, a positive (or negative) attitude formed initially, does not always lead, contrary to what was assumed, to a positive (or negative) assessment of the whole text and its message.
THE PRIMACY EFFECT IN PRESS PUBLICATIONS